The TBP-like factor: an alternative transcription factor in Metazoa? - Dantonel, J.C.; Wurtz, J.M.; Poch, O.; Moras, D.; Tora, L. (Trends in Biochemical Sciences, 1999)
Protein sequence analysis has revealed a family of TATA-binding-protein (TBP)-like factors (TLFs) in metazoan organisms. Modelling of the three-dimensional structure of these TLFs suggests that they form an asymmetric saddle-like structure and that, unlike TBP, TLFs might bind to DNA sequences other than classical TATA boxes. Thus, the existence of TLFs presents a challenge to the doctrine that TBP is a universal regulator of transcription in metazoans.